Changes in Subbaccalaureate Career and Technical Education Attainment Over Time and Across "Special Populations" - Cameron Sublett; Jay Plasman (Journal of Postsecondary Student Success)
Recent changes to federal career and technical education (CTE) policy have emphasized the importance of closing access and success gaps in postsecondary CTE among “special” student populations including low-income students, racially minoritized students, students with disabilities, and student groups historically underrepresented in nontraditional educational pipelines. Using two nationally representative samples of first-time, subbaccalaureate students, the current study sought to assess the degree to which certificate and associate degree completions in CTE areas of study have changed over time and the degree to which changes over time are moderated by special population membership. Overall, there is some evidence to suggest CTE completions have changed materially over time; however, we find considerable variation across CTE clusters and special populations.